2015
DOI: 10.1159/000375376
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Remineralization of Human Enamel in the Presence of Polyamidoamine Dendrimers in vitro

Abstract: Poly(amidoamine) (PAMAM) dendrimers, known as artificial proteins, have unique and well-defined molecular size and structure. It has previously been used to mimic protein-crystal interaction during biomineralization. In this study, generation 4.5 (4.5G) PAMAM with carboxylic acid (PAMAM-COOH) was synthesized and utilized to remineralize the surface of etched enamel in vitro. Using confocal laser scanning microscopy, Fourier transform infrared spectroscopy, X-ray diffraction analysis and scanning electron micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 29 publications
0
32
0
3
Order By: Relevance
“…These amelogenin-inspired dendrimers have been referred to as "artificial proteins" as they can mimic the functions of organic matrices in modulating the biomineralization of tooth enamel. Several in vitro studies have demonstrated that amphiphilic, carboxyl-terminated, and phosphateterminated PAMAM dendrimers exhibited a strong tendency to self-assemble into hierarchical enamel crystal structures [Chen et al, , 2014[Chen et al, , 2015Wu et al, 2013;Yang et al, 2011]. The new crystals created by the PAMAM organic templates had the same structure, orientation, and mineral phase of the intact enamel, with the HA nanorods closely paralleling the original prisms .…”
Section: Amelogeninmentioning
confidence: 99%
“…These amelogenin-inspired dendrimers have been referred to as "artificial proteins" as they can mimic the functions of organic matrices in modulating the biomineralization of tooth enamel. Several in vitro studies have demonstrated that amphiphilic, carboxyl-terminated, and phosphateterminated PAMAM dendrimers exhibited a strong tendency to self-assemble into hierarchical enamel crystal structures [Chen et al, , 2014[Chen et al, , 2015Wu et al, 2013;Yang et al, 2011]. The new crystals created by the PAMAM organic templates had the same structure, orientation, and mineral phase of the intact enamel, with the HA nanorods closely paralleling the original prisms .…”
Section: Amelogeninmentioning
confidence: 99%
“…Up to now the vast majority of the studies with dendritic derivatives addressed the mineralization of CP in bulk aqueous solution for mimicking the effect of noncollagenous proteins, that is, the water‐soluble fraction of proteins. Other studies focused on in vitro remineralization of CP‐based composites such as dentine and enamel . These studies involved various types of dendrimers such as carboxylic acid‐terminated poly(amidoamine) (PAMAM) dendrimers, amine terminated dendrimers such as PAMAM, poly(propylene imine) (PPI), and branched poly(ethylene)imine (PEI), hydroxyl‐terminated PAMAM, and phosphate‐terminated PAMAM .…”
Section: Introductionmentioning
confidence: 99%
“…Other studies focused on in vitro remineralization of CP‐based composites such as dentine and enamel . These studies involved various types of dendrimers such as carboxylic acid‐terminated poly(amidoamine) (PAMAM) dendrimers, amine terminated dendrimers such as PAMAM, poly(propylene imine) (PPI), and branched poly(ethylene)imine (PEI), hydroxyl‐terminated PAMAM, and phosphate‐terminated PAMAM . Several other studies addressed the interaction of these and other polymers with CP crystals, mostly to evaluate the interaction of the terminal functional groups with the CP surface …”
Section: Introductionmentioning
confidence: 99%
“…However, due to the lack of an affinity for the enamel surface and self-assembly ability, these ACP nanoparticles cannot efficiently adsorb on the surface of enamel and transform into the oriented and ordered HAP crystals to remineralize enamel. More recently, it has been demonstrated that carboxyl-terminated poly(amido amine) (PAMAM-COOH) can promote the HAP crystallization process and thus has potential for the remineralization of dental hard tissues29. Furthermore, alendronate (ALN) is conjugated on PAMAM-COOH, causing increased binding strength between PAMAM-COOH and the enamel surface due to its specific adsorption on HA (the primary component of tooth enamel)30.…”
mentioning
confidence: 99%